2019
DOI: 10.21887/ijvsbt.15.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Herbal Galactogogue (Sanjivani biokseera) on Milk Yield and Milk Constituents in Lactating Kankrej Cattle at Organised Farm

Abstract: The study was conducted to evaluate the effect of feeding herbal galactogogue preparation (Sanjivani biokseera) on the milk yield and milk constituents in lactating Kankrej cows. Thirty-two lactating Kankrej cows in their 1st to 6th lactation were taken for the experiment from 3 days after calving up to 52 days postpartum. All the animals were fed as per the standard seasonally available roughages and concentrates to meet their nutritional requirements. The cows were randomly divided into two uniform groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…According to Mohanty et al [2014], herbs with galactagogue properties include goat's rue, nettle, caraway, and common hops. Many studies [Grabowicz et al 2004, Prayitno et al 2016, Panchasara et al 2019 indicate that the use of herbs in the diet of ruminants improves feed conversion and production results, beneficially modifies the bacterial microbiome of the rumen, and affects the immune system. The authors found that the administration of herb supplements to cows increased milk yield and improved the quality of the milk.…”
Section: Phytobioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Mohanty et al [2014], herbs with galactagogue properties include goat's rue, nettle, caraway, and common hops. Many studies [Grabowicz et al 2004, Prayitno et al 2016, Panchasara et al 2019 indicate that the use of herbs in the diet of ruminants improves feed conversion and production results, beneficially modifies the bacterial microbiome of the rumen, and affects the immune system. The authors found that the administration of herb supplements to cows increased milk yield and improved the quality of the milk.…”
Section: Phytobioticsmentioning
confidence: 99%
“…High-quality bulky and concentrate feeds are often insufficient for a balanced feed ration that meets the nutritional requirements of a high-producing cow. For this reason, feeding solutions are sought that will allow the production potential of the cow to be fully exploited while limiting the occurrence of metabolic disease and improving reproductive parameters [Čermáková et al 2012, Prayitno et al 2016, Mobeen et al 2019, Callaway et al 2019, Panchasara et al 2019]. The most problematic period in the feeding of high-producing dairy cows is the perinatal period, which determines milk production throughout lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Even their low concentrations in feed mixtures have an impact on the antioxidant indices in lactating dairy cows. Animals whose diets were supplemented with herbs exhibited an increase in the activation of antioxidant enzymes in both blood and milk, which play an important role in cell protection against oxidative damage [ 25 , 26 , 27 ]. Many studies have demonstrated that herbs used in the diet for ruminants have a beneficial effect, as they improve the feed conversion efficiency, modify the rumen microflora, and, consequently, improve animal health and performance [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animals whose diets were supplemented with herbs exhibited an increase in the activation of antioxidant enzymes in both blood and milk, which play an important role in cell protection against oxidative damage [ 25 , 26 , 27 ]. Many studies have demonstrated that herbs used in the diet for ruminants have a beneficial effect, as they improve the feed conversion efficiency, modify the rumen microflora, and, consequently, improve animal health and performance [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Better production results are achieved upon application of herbal blends rather than individual herbs, mainly due to the synergistic effect of their active compounds [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Employing natural medical herbal additives as feed additives for animals represents a promising alternative to antibiotics, promoting animal health and performance while addressing concerns related to antibiotic resistance and animal production sustainability. Supplementing animal diets with herbs, even at low concentrations in feed mixtures, has been shown to increase the activation of antioxidant enzymes in both blood and milk, which are essential for safeguarding cells against oxidative damage (Panchasara et al, 2019;Vizzotto et al, 2021;Kolling et al, 2022;Stobiecka et al, 2023). Alongside this, previous studies indicated that incorporating herbs into ruminant diets offers various benefits.…”
Section: Introductionmentioning
confidence: 99%